The Role of the Principal in Optimizing Online-Based Learning at SMA Negeri 3 Kayuagung - Patraliza, Hellen; Putra, Alhadi Yan; Mahasir, Mahasir (Journal of Social Work and Science Education, 2023)
This study aims to describe and find out the role of the school principal in optimizing online-based learning at SMA Negeri 3 Kayuagung. Data collection tools using interviews, documentation, observation, and literature review. Data analysis used descriptive qualitative analysis with research stages referring to Miles and Huberman’s theory, namely data collection, data reduction, data presentation, and concluding. The results of the study stated that the role of the principal in optimizing online learning at SMA Negeri 3 Kayuagung was carried out by 1) setting online learning standards; 2) building effective communication between teachers and parents; 3) improving teachers’ ability to manage online learning at SMA Negeri 3 Kayuagung. The obstacles encountered were the use of learning media and the limited methods used in the online learning process and the evaluation of learning outcomes. The solution taken is to, among other things, carry out teacher competence development in supervising and training online learning.